¿Tiene el homo oeconomicus sentido del deber? - Zamora Bonilla, Jesús Pedro (ENDOXA, 2004)
I invite readers to read this paper on 'Kantian ethics, 'economic rationality, the 'sense of duty, 'categorical imperatives', and so on, and answer whether they think it should have an abstract at all.